Brand Image as a Mediator of the Effect of Product Quality and Social Media Marketing on Consumer Purchasing Decisions in Endek MSMEs - Komang Adi Gunawan; Ni Luh Wayan Sayang Telagawathi; Ni Made Ary Widiastini (MEC-J (Management and Economics Journal), 2026)
Digitalization has reshaped consumer behavior, yet prior studies show inconsistent evidence on whether brand image mediates the effects of social media marketing and product quality on purchasing decisions. This study examines these relationships in Endek MSMEs in Seririt District using a quantitative approach with SEM-PLS on 100 respondents. The results show that social media marketing and product quality significantly affect purchasing decisions, both directly and through brand image, which also exerts a strong independent influence. The study clarifies previous mediation inconsistencies and contributes practical insights for strengthening MSME competitiveness through improved digital marketing and product quality.